Partial characteristics of hemolytic factors secreted from airborne Aspergillus and Penicillium, and an enhancement of hemolysis by Aspergillus micronesiensis CAMP-like factor via Staphylococcus aureus-sphingomyelinase - Sumonrat Kaveemongkonrat (2020)
© 2019, The Microbiological Society of Korea. One of the advantages for initial survival of inhaled fungal spores in the respiratory tract is the ability for iron acquisition via hemolytic factor-production. To examine the ability of indoor Aspergillus and Penicillium affecting hemolysis, the secreted factors during the growth of thirteen strains from eight species were characterized in vitro for their hemolytic activity (HA) and CAMP-like reaction. The hemolytic index of HA on human blood agar of Aspergillus micronesiensis, Aspergillus wentii, Aspergillus westerdijkiae, Penicillium citrinum, Penicillium copticola, Penicillium paxilli, Penicillium steckii, and Penicillium sumatrense were 1.72 ± 0.34, 1.61 ± 0.41, 1.69 ± 0.16, 1.58 ± 0.46, 3.10 ± 0.51, 1.22 ± 0.19, 2.55 ± 0.22, and 1.90 ± 0.14, respectively. The secreted factors of an Aspergillus wentii showed high HA when grown in undernourished broth at 25°C at an exponential phase and were heat sensitive. Its secreted proteins have an estimated relative molecular weight over 50 kDa. Whereas, the factors of Penicillium steckii were secreted in a similar condition at a late exponential phase but showed low HA and heat tolerance. In a CAMP-like test with sheep blood, the synergistic hemolytic reactions between most tested mold strains and Staphylococcus aureus were identified. Moreover, the enhancement of α-hemolysis of Staphylococcus aureus could occur through the interaction of Staphylococcus aureus-sphingomyelinase and CAMP-like factors secreted from Aspergillus micronesiensis. Further studies on the characterization of purified hemolytic- and CAMP-like-factors secreted from Aspergillus wentii and Aspergillus micronesiensis may lead to more understanding of their involvement of hemolysis and cytolysis for fungal survival prior to pathogenesis.